Peningkatan Keselamatan Gedung melalui Pemeriksaan MEP dalam Proses Sertifikat Laik Fungsi (SLF) - Yuli Prasetyo; Basuki Winarno; Kumala Mahda H; Ryan Wicaksono; R. Oktav Yama; Narava Kansha Putra P (Lembaga Pengembangan Kinerja Dosen, 2025)
This activity begins with checking the mechanical, electrical, and plumbing (MEP) systems at the Gunung Mas Building in Madiun City, to assist in the process of issuing a Certificate of Functional Worthiness (SLF). The inspection included electrical power capacity, main distribution panels (MDP and SDP), lightning protection systems, light fire extinguishers (APAR), and pipe or plumbing installations such as clean water channels, waste water channels, and rain drainage. The results showed that the installed power was 105 KVA from PLN, the distribution panel, and cable sizes generally met safety standards (SNI and IEEE). However, several problems were found such as a load imbalance exceeding 10%, the lack of measuring instruments on the panel, and cable sizes that needed to be adjusted to the rating of the protective device. Plumbing installations such as a clean water source with a 2000 liter roof tank, waste disposal to a septic tank, and rainwater channels to the city channel were still running well, although repairs were needed to the bathroom in the putty area. Overall, the building was declared suitable, with recommendations for improving load distribution, adjusting cable sizes, and routine maintenance.